A case report of visceral leishmaniasis in the Tharaka District, Kenya - Pelizzi, M.; Verna, M.; Vanelli, M. (Acta Biomedica Atenei Parmensis, 2006)
Leishmaniasis is a parasitic disease that is transmitted through a bite of some species of sandflies. It is caused by obliged intra-cellular protozoa of the genus Leishmania and is responsible for a broad spectrum of clinical syndromes: cutaneous leishmaniasis (CL), visceral leishmaniasis (VL) and mucocutaneous leishmaniasis (ML). The visceral disease (classically known as “kala azar”) is the most aggressive form and if undervalued is fatal. Here we describe the first case of visceral leishmaniasis in the Tharaka District reported in literature.